Religion and Disability: The Experiences of Families of Children with Special Needs - O'Hanlon, Elizabeth E. (Journal of religion, disability & health, 2013)
This investigation examined experiences of families of children with disabilities in their spiritual communities. Using the Spiritual Community Experiences Inventory, parents rated importance of and satisfaction with clergy, various religious activities, and support received from clergy and spiritual community members. Families reported that participation in religious activities and support from clergy and members were important. Moreover, families were highly satisfied with these activities and support. As predicted, a significant relationship was found between frequency of attendance, amount of support, and satisfaction with activities and support. Only in the case of formal ceremonies was the frequency/satisfaction relationship not significant.